On crushing behavior of square aluminum/CFRP hybrid structures subjected to quasi-static loading. (March 2023) - Zhu, Guohua; Zhao, Zhonghao; Cao, Xi-Ao; Wei, Lulu; Wang, Zhen; Zhao, Xuan
Abstract: Metal/composite hybrid thin-walled structures exhibit tremendous merits on the balance design among material costs, weight reduction and mechanical performances. In spite of these advantages, their underlying energy dissipating mechanisms and the influence law of key factors (such as mechanical properties, hybrid ratio, loading angle, etc.) on crushing behavior are still not well illustrated. This study aims to comprehensively explore the crushing deformation characteristics and underlying energy dissipating mechanisms of various square aluminum/CFRP hybrid structures (i.e., aluminum tube internally strengthened with CFRP namely CFRP/AL; aluminum tube externally strengthened with CFRP namely AL/CFRP tubes). Specifically, several axial quasi-static compression tests are performed to compare crushing behavior and performances of between hybrid tubes together with the corresponding net aluminum and CFRP tubes. Experimental results indicate that the total energy absorption of the CFRP/AL hybrid tubes is considerably higher than that of the summation of corresponding individual tubes. Subsequently, finite element models are developed for CFRP/AL hybrid columns to explore the underlying energy-absorbing mechanisms (the contribution of each constituent part on total energy absorption) and the influence law of key factors (mechanical properties, hybrid ratio, loading angle), which cannot be observed from experimental results. Numerical results indicate that the main reasons for the improvement in total energy absorption of CFRP/AL hybrid tubes are the altered deformation pattern of the outer aluminum tube and the significantly increased friction energy. Further, their outer aluminum tube seems to be more likely to generate plastic folding deformation rather than splaying progressive failure mode with increasing initial yield stress. The hybrid ratio and CFRP layer thickness jointly determine the deformation pattern of the CFRP/AL hybrid columns. Finally, it is also found that the load carrying capacity and energy-absorbing characteristics of CFRP/AL hybrid columns gradually reduce with increasing loading angle. The present study is expected to illustrate the potential of such hybrid structure as a crashworthy device and offer some design guidance for application and dissemination. Highlights: Crushing behavior of square aluminum/WF-CFRP hybrid structures under axial and oblique loading are investigated. The underlying energy dissipating mechanisms of square aluminum/WF-CFRP hybrid columns are explored. The influence mechanisms on crushing behavior of aluminum/WF-CFRP hybrid structures are illustrated.